(untitled) (Biological Sciences - PJSIR, 2006)
Phenol and its derivatives were removed by the physical treatment process of adsorption from pharmaceutical industrial wastewaters at the laboratory scale. The adsorption relationship between different doses of activated carbon and the concentrations of the phenolic compounds adsorbed was studied with respect to time. Determination of phenol concentration was carried out before and after adsorption on activated carbon by the red colour reaction spectro- photometerically. In this reaction, 4-aminoantipyrine acted as a colouring agent, potassium ferricyanide as an oxidant, and ammonium hydroxide-ammonium chloride as the buffer solution. During the present studies, the adsorption process using activated charcoal resulted in the reduction of phenol from 315 mg/l to 0.1 mg/l.